The Effects of Doses and Methods of Lime Placement to N, P, K, Ca, Mg Content and Sugarcane Growth in Ultisol Lampung Tengah, Indonesia - Heri Wahyudi; Azwar Ma’as; Eko Hanudin; Sri Nuryani Hidayah Utami (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
Land circumstances on Seputih Mataram, Lampung included in dried area which is consist of Ultisols soil (soil taxonomy). Ultisol consist of H2O which has pH of less than 5.5. It will cause the amount of soil nutrient that absorbed is not optimal yet. This research aimed to know the influence of adding dolomite to the soil chemical content (pH number of H2O, KCl, content of total N, available P, exch-K, exch-Ca, exch-Mg, Organic-C, ratio C/N, exch-Al, exch-H, CEC), nutrient content on the leaf (such as N, P, K, Ca, Mg) and sugar cane physic. This research used Completely Randomized Design 2 factors with 3 blocks repetition. First factor was the dolomite doses in six contents: without the dolomite (K0), 500 kg/ha (K1), 1000 kg/ha (K2), 2000 kg/ha (K3), 4000 kg/ha (K4) and 6000 kg/ha (K5). The second factor (R) was the depth of dolomite placement, consist of: (R1) dolomite with 0-20 cm depth and (R2) dolomite with 20-40 cm depth. The observation used to know the soil chemical content, the leaf nutrients and the variables that used into the research. The observation results variant analyzed (ANOVA) in 5 % and continued with the Duncan’s Multiple Range Test (DMRT) in 5 % if the result showed the real differentiation. The result showed that the depth of dolomite was not real influence to the amount of Nitrogen (N), Phosphorus (P), Potassium (K), Calcium (Ca), and Magnesium (Mg) in leaf. Dolomite addition was real influence for Calcium (Ca) uptake in leaf, but it was not real influenced the leaf uptake. Dolomite addition was real influence in the leaf content and leaf Magnesium (Mg) uptake. 6000 kg/ha dolomite for physical soil characteristic ( pH H2O, pH KCL, C/N ratio, K, P, Ca, Mg,Exch-H), leaf nutrient ( N, K, Ca), Mg and Ca uptake on leaf also sugar cane tonnage per hectare showed the maximum result.